2013
DOI: 10.1017/s0266467413000679
|View full text |Cite
|
Sign up to set email alerts
|

Variation in savanna vegetation on termite mounds in north-eastern Namibia

Abstract: Abstract:In savanna, termite mounds support more diverse vegetation than off-mound areas, but little is known of the patterns in plant assemblages on mounds. To explain vegetation differentiation between (1) component structures of termite mounds (conical centre vs. pediment), (2) active and inactive mounds (termites present vs. termites absent), and (3) sites on and off mounds (on mounds vs. surrounding savanna), species composition, richness and abundances of woody plants were recorded on 70 mounds and in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, germination and establishment should be ex amined as processes after seed dispersal. Although some trees were established on the cones of active mounds, the cones have greater soil hardness and consequently suppress the establishment of woody plants (Yamashina 2013). Therefore, particular plant traits, such as the dynamics of root system development and germination, might explain plant preferences for mounds as habitat.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, germination and establishment should be ex amined as processes after seed dispersal. Although some trees were established on the cones of active mounds, the cones have greater soil hardness and consequently suppress the establishment of woody plants (Yamashina 2013). Therefore, particular plant traits, such as the dynamics of root system development and germination, might explain plant preferences for mounds as habitat.…”
Section: Discussionmentioning
confidence: 99%
“…• Studies analyzing the spatial distribution of species on mounds have shown spatial differentiation within mound microhabitats (Lawson & Jenik 1967;Kirchmair et al 2012;Yamashina 2013), offering soil properties, microclimatic effects and protection from fire as possible explanations for the spatial distribution of species on mounds.…”
Section: Differences Between Mounds and The Surrounding Savannamentioning
confidence: 99%
“…J. Kirk ex J. Léonard) woodland (White 1984). Although C. mopane is a dominant species both on and off termite mounds, there is higher density and species richness of woody plants on these mounds than in the surrounding savannah matrix (Yamashina 2013). Avian seed dispersal may contribute to this unique woody plant community (Yamashina 2014); however, clear evidence is lacking.…”
Section: Introductionmentioning
confidence: 99%